Monetary policy and the stock market structure: some international empirical evidence - Alovokpinhou, Sedjro Aaron (My University, 2016)
This paper builds upon Blanchard's (1981) model of asset prices, and provides an empirical evidence for good news cases (GNC) and/or bad news cases (BNC) as de ned in Blanchard's paper. We update Blanchard's model by introducing Taylor's rule of monetary policy and explicitly incorporate income distribution in a small, open economy. The ndings indicate that, the labour share is a strong and signi cant variable that should be considered in asset pricing models. The real exchange rate plays a signi cant role in the determination of asset prices in most of the selected countries, but the signi cance is stronger in the emerging markets economies. As the main objective of the paper, the study has found four of the selected countries to be bad news cases and eight of them are good news cases.
Thesis (M.M. (Finance & Investment)--University of the Witwatersrand, Faculty of Commerce, Law and Management, Wits Business School, 2016.
Keywords: Stocks--Prices--Mathematical models; Monetary policy; Econometrics